Faktor risiko yang mempengaruhi disfungsi tuba Eustachius pada penderita rinitis alergi persisten - Novina Rahmawati; Suprihati Suprihati; Muyassaroh Muyassaroh (PERHATI-KL, 2011)
Background: Persistent allergic rhinitis (AR) can lead to Eustachian tuba dysfunction. It could beinfluenced by many factors. Purpose: To prove that AR’s degree, duration, presence of chronic tonsillitisand the use of air conditioner are the risk factors of the Eustachean tube dysfunction in patients withpersistent allergic rhinitis. Method: A cross-sectional study was conducted on patients between 11-54years age who came with persistent AR. Tubal dysfunction was detected by tympanometric examination (MEP negative <-25 mmH2O). The data analysis was analyzed using Chi square test and prevalence ratio. Results: There were 68 subjects. The largest age group was 23-34 years old with mean age is 27.8years. Twenty-six patients (32,8%) with persistent AR had tubal dysfunction. Chi square test for persistentAR’s degree, duration of AR and presence of chronic tonsillitis had no significant relationship with tubaldysfunction. The use of AC was significantly correlated with tubal dysfunction (p>0.05). Multivariatelogistic regression analysis found that it became a risk factor for tubal dysfunction p= 0.019, RP=5.446, CI 95%= 1.321- 22.575. Conclusion: The use of AC becomes a risk factor for tubal dysfunctionin patients with persistent allergic rhinitis. Keywords: persistent allergic rhinitis, Eustachean tube dysfunction, tympanometry Abstrak : Latar belakang: Rinitis alergi (RA) persisten dapat menimbulkan disfungsi tuba Eustachius. Disfungsituba dapat dipengaruhi oleh beberapa faktor. Tujuan: Membuktikan bahwa derajat RA, lama sakit RA,keberadaan tonsiltis kronik dan pemakaian air conditioner (AC) merupakan faktor risiko terjadinyadisfungsi tuba pada penderita rinitis alergi persisten. Metode: Penelitian dengan metode potong-lintangpada RA persisten usia 11-54 tahun. Disfungsi tuba ditentukan dengan pemeriksaan timpanometri (MEPnegatif/<-25 mmH2O). Analisis hasil dengan uji Chi square dan rasio prevalensi. Hasil: Didapatkan68sampel. Usia terbanyak 23-34 tahun, rerata usia 27,8 tahun. Penderita RA persisten dengan disfungsituba 26 (38,2%). Uji Chi square didapatkan derajat RA persisten, lama sakit dan keberadaan tonsilitiskronik tidak mempengaruhi disfungsi tuba (p>0,05). Analisis regresi logistik multivariate didapatkanpemakaian AC secara independen mempunyai risiko terjadinya disfungsi tuba p=0,019, RP=5,446, CI95%= 1,321-22,575. Kesimpulan: Pemakaian AC merupakan faktor risiko terjadinya disfungsi tubapada penderita rinitis alergi persisten. Kata kunci: rinitis alergi persisten, disfungsi tuba, timpanometri